Effectiveness of caudal septal extension graft application in endonasal septoplasty - Karadavut,Yunus (2017)
Abstract Introduction Septal deviation is a common disease seen in daily otorhinolaryngology practice and septoplasty is a commonly performed surgical procedure. Caudal septum deviation is also a challenging pathology for ear, nose, and throat specialists. Many techniques are defined for caudal septal deviation. Objective To evaluate the effectiveness of caudal septal extension graft (CSEG) application in patients who underwent endonasal septoplasty for a short and deviated nasal septum. Methods Forty patients with nasal septal deviation, short nasal septum, and weak nasal tip support who underwent endonasal septoplasty with or without CSEG placement between August 2012 and June 2013 were enrolled in this study. Twenty patients underwent endonasal septoplasty with CSEG placement. The rest of the group, who rejected auricular or costal cartilage harvest for CSEG placement, underwent only endonasal septoplasty without any additional intervention. Using the Nasal Obstruction Symptom Evaluation (NOSE) and Rhinoplasty Outcome Evaluation (ROE) questionnaires, pre- and post-operative acoustic rhinometer measurements were evaluated to assess the effect of CESG placement on nasal obstruction. Results In the control group, preoperative and postoperative minimal cross-sectional areas (MCA1) were 0.44 ± 0.10 cm2 and 0.60 ± 0.11 cm2, respectively (p < 0.001). In the study group, pre- and postoperative MCA1 values were 0.45 ± 0.16 cm2 and 0.67 ± 0.16 cm2, respectively (p < 0.01). In the control group, the nasal cavity volume (VOL1) value was 1.71 ± 0.21 mL preoperatively and 1.94 ± 0.17 mL postoperatively (p < 0.001). In the study group, pre- and postoperative VOL1s were 1.72 ± 0.15 mL and 1.97 ± 0.12 mL, respectively (p < 0.001). Statistical analysis of postoperative MCA1 and VOL1 values in the study and the control groups could not detect any significant intergroup difference (p = 0.093 and 0.432, respectively). In the study group, mean nasolabial angles were 78.15 ± 4.26º and 90.70 ± 2.38º, respectively (p < 0.001). Conclusion Endonasal septoplasty with CESG placement is an effective surgical procedure with minimal complication rate for subjects who have a deviated, short nasal septum and weak nasal tip support.